Outcome of Stented Versus Non-Stented Ureteroscopic Lithotripsy - M. SHAHID LATIFE RAHAT USMAN M. NAWAZ, M. YOUNIS (Journal of Fatima Jinnah Medical University, 2018)
Ureteroscopy has been recognized as a major method for treating ureteric calculi. Although invasive, the development of smaller and more flexible ureteroscopes, and a new generation of various intracorporial lithotripters, has made this procedure safer and more effective. Recently ureteroscopy has been sued to treat stones in the ureter as well as those in the kidneys . Stenting has been primarily used to treat urinary obstruction and the frequency of this use is increasing with the increase in ureteroscopic management. Objective: To compare the outcome of stenting versus non-stenting in ureteroscopic lithotripsy in patients with ureteric stone causing obstruction. Study Design: Interventional study; randomized clinical trial. Setting: Study was carried out in Department of Urology, Mayo Hospital, Lahore. Study Duration: Six months (15th August, 2008 to 15th February, 2009) Material and Methods: One hundred patients diagnosed of ureteric calculi were divided into two groups A and B; Group A included the patients who have stent after ureteroscopic lithotripsy and group B included patients who have non-stented ureteroscopic lithrotripsy. Outcome was recorded in 7 days after ureteroscopy and measured postoperatively. Results: Out of these 100 subjects, 39 were males and 11 were females in group A while 37 males and 13 females in group B. It has been observed that most of the patients fall in age group 31-45 years. There were 13 patients of no urgency in group A and 32 patients in group B. There were mild pain in 29 patients in group A and 23 patients of group B. Urinary tract infection was noted in 6 patients of group A and 5 patients of group B.Mild haematuria was present in28 patients of group A as compared to 12 patients of group B . Conclusion: Patients with stents seem to have significantly more bladder and lower urinary tract symptoms than those in whom stents are not placed.